2019
DOI: 10.3390/pharmacy7030135
|View full text |Cite
|
Sign up to set email alerts
|

Macrolide Allergic Reactions

Abstract: Macrolides are antimicrobial agents that can be used to treat a variety of infections. Allergic reactions to macrolides occur infrequently but can include minor to severe cutaneous reactions as well as systemic life-threatening reactions such as anaphylaxis. Most reports of allergic reactions occurred in patients without prior exposure to a macrolide. Cross-reactivity among macrolides may occur due to the similarities in their chemical structures; however, some published literature indicates that some patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 118 publications
(154 reference statements)
0
17
0
Order By: Relevance
“…1 This group of antibiotics includes 14-membered lactones (erythromycin, roxithromycin, clarithromycin), 15membered lactones (azithromycin), ketolides (telithromycin), and 18-membered lactones (fidaxomicin). 2,3 Fidaxomicin is indicated for the treatment of Clostridium difficile-associated diarrhea in adults, while all other macrolides may be used in the treatment of a variety of infections including respiratory tract infections, skin and soft tissue infections, pelvic inflammatory disease, as well as to eradicate Helicobacter pylori. 1,2 In several studies, macrolides were identified as one of the classes of antibiotics which are associated with the occurrence of Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN, formally known as Lyell syndrome).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…1 This group of antibiotics includes 14-membered lactones (erythromycin, roxithromycin, clarithromycin), 15membered lactones (azithromycin), ketolides (telithromycin), and 18-membered lactones (fidaxomicin). 2,3 Fidaxomicin is indicated for the treatment of Clostridium difficile-associated diarrhea in adults, while all other macrolides may be used in the treatment of a variety of infections including respiratory tract infections, skin and soft tissue infections, pelvic inflammatory disease, as well as to eradicate Helicobacter pylori. 1,2 In several studies, macrolides were identified as one of the classes of antibiotics which are associated with the occurrence of Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN, formally known as Lyell syndrome).…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Fidaxomicin is indicated for the treatment of Clostridium difficile-associated diarrhea in adults, while all other macrolides may be used in the treatment of a variety of infections including respiratory tract infections, skin and soft tissue infections, pelvic inflammatory disease, as well as to eradicate Helicobacter pylori. 1,2 In several studies, macrolides were identified as one of the classes of antibiotics which are associated with the occurrence of Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN, formally known as Lyell syndrome). 4,5 SJS and TEN (SJS/TEN) are rare acute severe, potentially life-threatening, mucocutaneous hypersensitivity reactions characterized by epidermal necrosis and detachment.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hypersensitivity reactions resulting from macrolide use occur infrequently (0.4%-3%). 6 It was hypothesized that the skin rash in macrolides use could result from infection-mediated immunomodulation or due to an altered drug metabolism caused by the disease. 7 Incidence of hypersensitivity reactions with cephalosporins is reported to be 1% to 3%.…”
Section: Discussionmentioning
confidence: 99%